Posaconazole in lung transplant recipients: use, tolerability, and efficacy. Issue 2 (22nd February 2016) - Robinson, C.L.; Chau, C.; Yerkovich, S.T.; Azzopardi, M.; Hopkins, P.; Chambers, D.
Abstract: Background: Fungal infection is a common cause of mortality and morbidity in lung transplant recipients (LuTR). Treatment failure to first‐line antifungals because of resistance or intolerance is an increasing problem. Posaconazole (PCZ), a triazole antifungal, is an attractive treatment option. Methods: We performed a single‐center retrospective study to describe the use, tolerability, efficacy, and drug interaction effect (with tacrolimus) of PCZ oral suspension in LuTR. Results: Seventy‐eight patients were treated with PCZ oral suspension for prophylaxis ( n = 15), pre‐emptive treatment ( n = 31), and treatment of possible ( n = 7) and probable ( n = 25) invasive fungal infection. A range of fungal isolates was encountered. Resolution was observed in 52.4% (probable, possible, and pre‐emptive treatment groups). Aggregate all‐cause 1‐year mortality was 12.8%. PCZ was well tolerated with 11.5% of patients experiencing adverse effects. Despite dose adjustment strategies, 11.7% of patients experienced supratherapeutic tacrolimus levels, which in 5 cases was associated with a rise (mean 21.6 μmol/L) in serum creatinine. Conclusions: PCZ is well tolerated and appears effective in the management of fungal infection after lung transplantation. Patients receiving concurrent tacrolimus require careful therapeutic drug monitoring.